2016
DOI: 10.1002/2016jd025030
|View full text |Cite
|
Sign up to set email alerts
|

Light absorption properties of brown carbon in the high Himalayas

Abstract: The light‐absorbing properties of water‐soluble brown carbon (WS‐BrC) and methanol‐soluble brown carbon (MeS‐BrC) were studied in PM10 aerosols collected at the “Nepal Climate Observatory‐Pyramid” (NCO‐P) station (5079 m above sea level) during the period 2013–2014. The light absorption coefficients of WS‐BrC and MeS‐BrC were the highest during the premonsoon season and the lowest during monsoon. MeS‐BrC absorbs about 2 times higher at 365 nm and about 3 times more at 550 nm compared to WS‐BrC. The mass absorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
70
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(97 citation statements)
references
References 65 publications
22
70
5
Order By: Relevance
“…Values of the mass absorption efficient at 365 nm (MAE 365 ), calculated from the ratio of the absorption coefficient at 365 nm and mass concentration of WSOC, recorded for the samples from these two sites, were 0.81 for QOMS and 0.48 for WLG, respectively. The MAE 365 of the QOMS samples in our study is similar to that reported previously (0.66-0.72 m 2 g −1 ) for the same area of study-the Himalayas (Kirillova et al, 2016). These MAE 365 values are significantly lower than those characteristic for fresh and/or less aged aerosol in urban areas of Beijing during winter (1.26), but close to the values reported during summer (0.52) (Du et al, 2014).…”
Section: Light Absorption Properties Of Wsocsupporting
confidence: 89%
See 2 more Smart Citations
“…Values of the mass absorption efficient at 365 nm (MAE 365 ), calculated from the ratio of the absorption coefficient at 365 nm and mass concentration of WSOC, recorded for the samples from these two sites, were 0.81 for QOMS and 0.48 for WLG, respectively. The MAE 365 of the QOMS samples in our study is similar to that reported previously (0.66-0.72 m 2 g −1 ) for the same area of study-the Himalayas (Kirillova et al, 2016). These MAE 365 values are significantly lower than those characteristic for fresh and/or less aged aerosol in urban areas of Beijing during winter (1.26), but close to the values reported during summer (0.52) (Du et al, 2014).…”
Section: Light Absorption Properties Of Wsocsupporting
confidence: 89%
“…The absorption coefficient of WSOC at QOMS was significantly higher than that of WLG although the concentration of WSOC at QOMS was lower than that at WLG. The MAE 365 of the QOMS samples in our study is similar to that reported previously (0.66-0.72 m 2 g −1 ) for the same area of study-the Himalayas (Kirillova et al, 2016). The absorption variation with respect to wavelength (AAE; absorption Ångström exponent) was determined from the slope of a linear regression fit of base 10 absorption coefficient versus wavelength within the range of 300 to 400 nm.…”
Section: Light Absorption Properties Of Wsocsupporting
confidence: 87%
See 1 more Smart Citation
“…Current BrC studies on the TP have mainly focused on the sources and optical properties of total BrC or extracted water‐/methanol‐soluble BrC and humic‐like substances (e.g., Kirillova et al, ; Li, Chen, et al, ; Li, Yan, et al, ; Wu et al, ; Zhu et al, , ). Here a statistical approach that we call the minimum R‐squared (MRS) method was developed to separate light absorption by secondary BrC versus primary BrC.…”
Section: Introductionmentioning
confidence: 99%
“…Fall was also the most variable season, with a 50% RSD, while MAE 365 values in the winter and spring were more consistent. In order to compare BC light absorption coefficient ( b abs ) at 678 nm ( λ of laser in Sunset OCEC carbon analyzer) with light absorption by BrC at 365 nm, the light absorption coefficient of BC at 365 was calculated using the power law wavelength dependence of b abs , using AAE BC = 1 [ Kirillova et al ., ]. Annually, WSOC BrC absorbs on average 3.4% relative to BC, ranging from 2.1% to 5.0% in the winter and summer respectively.…”
Section: Resultsmentioning
confidence: 99%